2015
DOI: 10.1016/j.jairtraman.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The strategic capability of Asian network airlines to compete with low-cost carriers

Abstract: a b s t r a c tNever before have network airlines been so exposed and vulnerable to low-cost carriers (LCCs). While LCCs had 26.3% of all world seats in 2013, Southeast Asia had 57.7% and South Asia 58.4% e and these figures will only increase. There are many consequences of LCCs on network airlines, including inadequately meeting the expectations of customers, so increasing dissatisfaction, and not offering sufficient value-for-money. Clearly, it is fundamentally important for Asian network airlines to respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, challenges may exist for future applications of this model, particularly in different markets where homogenised reporting is not available. Qualitative methods, particularly those employed by Pearson, O'Connell, Pitfield and Ryley (2015) and , can, therefore, be more effective where financial data is not available. Furthermore, the variables contained within the model are in no way exhaustive.…”
Section: Resultsmentioning
confidence: 99%
“…However, challenges may exist for future applications of this model, particularly in different markets where homogenised reporting is not available. Qualitative methods, particularly those employed by Pearson, O'Connell, Pitfield and Ryley (2015) and , can, therefore, be more effective where financial data is not available. Furthermore, the variables contained within the model are in no way exhaustive.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, research on the LCC industry has focused on competitive strategy analysis with traditional airlines [14][15][16][17] and route planning, which is different from traditional airlines [18,19], market research for customer characteristics [20], etc., and there has been less discussion on the operation and customer service of self-service technology. Moreover, few studies have used technology readiness as a segment variable to explore the market segmentation of self-service technology users.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have examined the role of price e convenience attributers (such as low ticket price and convenient booking channel) significantly affect customer intentions to travel via LCCs (Mikulic and Prebezac, 2011;O'Connell and Williams, 2005;Pearsona et al, 2015). Many studies have found evidence that external social support (e.g., positive word of mouth, mass media reports) (Kim and Lee, 2011;O'Connell and Williams, 2005;Saha and Theingi, 2009) and airline image (Chang and Hung, 2013;Yang et al, 2012) are important predictors of intentions to purchase LCCs.…”
Section: Introductionmentioning
confidence: 99%